KAJIAN PATI JAGUNG DAN BUNGA ROSELA PADA KUALITAS PERMEN LUNAK (soft candy) - HP, Sudaryati; Latifah, Ir; Sari, Yapri Lukita (REKAPANGAN, 2010)
Soft  candy is  mixtures  of  sucrose,  glucose  syrup,  water,  gel-forming  materials  and additives  such  as flavor,  dye  and  has  a  soft texture. Roselle  petals  become  alternative for the manufacture  of  soft  candy  roselle that  have  vitamin  C  and  anthocyanins  that  serves  as  a natural  red  color. This  soft  chewy  candy  is  produced  from  the  gel-forming  material.  Corn starch  as  a  gel-forming  material,  because  the  nature  of  corn  starch  in  its  contribution  to  the texture. Cooking is an important processing stage in the manufacture of candy that will affect the  texture  and  color  of  the  candies  are  produced.  This  study  aims  to  determine  the  effect  of adding corn starch and long ripening on the quality of roselle soft candy and to obtain the best combination  treatment  between  the  addition  of  corn  starch  and  long  cooking  in  the manufacture. This research method using a completely randomized design with 2 factors and repeated 3 times. The first factor was the concentration of corn starch (5%, 10%, 25%) and the second factor  is  the  length  of  cooking  (1.5  minutes,  3  minutes,  4.5  minutes).  The Best  research  results    soft  candy  corn  starch  concentration  of  10%  and  long  cooking  3 minutes to produce water content 5.712%, Vitamin C 27.78 mg/100gr, 56.060% total dissolved solids, texture 0.186 mm / gr.dtk and anthocyanin 0.0713%.Keywords: Software Candy, Rosela